Predictors of The Intention to Use The Internet for Purchasing - Wiyanti, Yeti Diah; Untoro, Wisnu (Jurnal Economia, 2016)
Abstract: Predictors of The Intention to Use The Internet for Purchasing. The purpose of this study was to examine and analyze the influence of intention to use the internet for purchasing. A survey methodology used to data from 160 Internet users students at the Sebelas Maret University which ever purchase online. SEM analysis show that the determinants of intention form: attitude, subjective norms, perceived behavioral control and trust have a significant effects on the intention to use the internet for purchasing unless the internet purchase experience have no significant effect on the intention to use the internet for purchasing and the determinants of intention form of: attitude, subjective norm, perceived behavioral control, internet purchase experience, and trust have a significant effects on the intention to use the internet for purchasing when moderated by the intention to use the Internet for information search.Keywords: Theory of Planned Behavior (TPB), internet purchase experience, trust, intention to use the internet.Abstrak: Prediktor Intensi Penggunaan Internet dalam Melakukan Pembelian Online. Tujuan penelitian ini adalah untuk menguji dan menganalisis pengaruh niat konsumen dalam menggunakan internet untuk melakukan pembelian online. Sebuah metodologi survei digunakan untuk mengumpulkan data 160 orang mahasiswa pengguna internet di Universitas Sebelas Maret Surakarta yang pernah melakukan pembelian online. Analisis SEM menunjukkan bahwa faktor-faktor penentu niat berupa: sikap, norma subjektif, kontrol perilaku yang dirasakan dan kepercayaan berpengaruh signifikan pada intensi penggunaan internet untuk melakukan pembelian kecuali pengalaman belanja online tidak berpengaruh signifikan terhadap intensi penggunaan internet untuk melakukan pembelian dan faktor-faktor penentu niat berupa: sikap, norma subjektif, kontrol perilaku yang dirasakan, pengalaman belanja online dan kepercayaan berpengaruh signifikan terhadap intensi penggunaan internet untuk melakukan pembelian ketika dimoderasi oleh intensi penggunaan internet untuk pencarian informasi.Kata kunci: Theory of Planned Behavior (TPB), pengalaman belanja online, kepercayaan, intensi penggunaan internet.